Mechanism and Sensitivity Analysis of Collapse in Large Section Mountain Neighborhood Tunnels - Zhang, Yongjun; Wang, Junyi; Liu, Fei; Xia, Huangshuai (Frontiers in Earth Science, 2022)
Collapse is one of the most frequent geological disasters in mountain tunnel engineering, posing major safety concerns for underground structures and construction crews. According to a catastrophic collapse in the shallow buried area of the Huangjiakuang tunnel in Weihai City, Shandong Province, the contributing factors, i.e., the surrounding rock property, influence of neighboring tunnel construction, and tunnel over-excavation are systematically investigated. The tunnel collapse, breaks through the ground surface, is inverted using MIDAS GTS NX. A tunnel deformation analysis model is created using the quantitative methods of grey relation analysis and entropy weight methods based on crown settlement and lateral wall horizontal contraction during tunnel excavation. The surrounding rock property, the distance between the left and right tunnel faces, and the over-excavation height have a significant effect on tunnel deformation, which are quantitatively interpreted by the tunnel deformation analysis model. This paper is valuable for the multi-factor analysis of tunnel deformation and determining the main contributing factors to the collapse quantitatively.